HUBUNGAN USIA IBU HAMIL DENGAN KEJADIAN PERSALINAN PREMATUR DI RSUD PANEMBAHAN SENOPATI BANTUL YOGYAKARTA: RELATIONSHIP BETWEEN THE AGE OF PREGNANT WOMEN AND PREMATURE LABOR IN PANEMBAHAN SENOPATI REGIONAL PUBLIC HOSPITAL, BANTUL, YOGYAKARTA - Rosyidah, Halimah; Kusumasari, RR Viantika; Adkhana, Dian Nur (Stikes Wira Medika Bali, 2019)
Premature delivery to global literature happening in the world, Indonesia occupies the fifth highest position. The cause of Multicomplex premature childbirth, one of the factors is age. Mother's age is at risk (< 20 and > 35 years), while age is not at risk (20-35 years). The purpose of this research is knowing the relationship between the age of pregnant women and the occurrence of premature labor. The study uses a descriptive correlation design with the Cross sectional approach. Sampling uses purposive sampling techniques with samples of 97 expectant mothers who have premature labor. Researchers use documentation studies from the medical record of Panembahan Senopati Yogyakarta in Bantul period from January to December 2018. Data analysis using Kendall-tau test. Generates a value of P Value 0046 (< 0, 05), which indicates there is a relationship between the age of pregnant women and the incidence of premature labor. Conclusion: There is a relationship between the age of pregnant women with the occurrence of premature delivery in the hospital Panembahan Senopati Bantul Yogyakarta.